2018
DOI: 10.1016/j.tcsw.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Lack of chitin synthase genes impacts capsular architecture and cellular physiology in Cryptococcus neoformans

Abstract: Highlights CHS genes and capsular architecture are linked in C. neoformans . CHS3 is the most important chitin metabolism gene linked to cryptococcal capsular structures. Lack of CHS genes affects extracellular vesicle formation and endogenous chitinase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
(86 reference statements)
1
14
0
Order By: Relevance
“…Cell wall thickness did not interfere with vesicle passage since C. albicans mutants with altered cell wall dimensions and composition were similar in both their in vitro susceptibility to liposomal amphotericin B and the ability of liposomes to penetrate the cell wall (Walker et al, ). This observation is in agreement with the fact that in C. neoformans chitin synthase mutants EV production and cell wall porosity had no apparent correlation (Rodrigues et al, ).…”
Section: Going Back Inside: Uptake Of Evs By Fungal Cellssupporting
confidence: 89%
“…Cell wall thickness did not interfere with vesicle passage since C. albicans mutants with altered cell wall dimensions and composition were similar in both their in vitro susceptibility to liposomal amphotericin B and the ability of liposomes to penetrate the cell wall (Walker et al, ). This observation is in agreement with the fact that in C. neoformans chitin synthase mutants EV production and cell wall porosity had no apparent correlation (Rodrigues et al, ).…”
Section: Going Back Inside: Uptake Of Evs By Fungal Cellssupporting
confidence: 89%
“…For instance, a C. neoformans mutant lacking a putative G 1 /S cyclin gene had increased production of EVs (Garcia-Rodas et al, 2014 ). Chitin synthase genes (CHS) were also suggested to play a role in vesicular release, as inferred from the observation that the deletion of chitin synthases genes in C. neoformans resulted in a significantly reduced release of EVs (Rodrigues et al, 2018 ). Recently, it was also shown that S. cerevisiae cytoplasmic organelles, called intracellular vesicle clusters (IVCs), serve as sites for the synthesis and selection of EV-associated proteins tagged for secretion (Winters et al, 2020 ).…”
Section: Biogenesis Selection Of Cargo and Release Of Evs In Fungimentioning
confidence: 99%
“…For the SEM, the treated H99 cells were washed with PBS and fixed by 2.5% glutaraldehyde. The specimens for SEM were prepared according to the standard sample preparation method as described ( 63 ). The gold-coated samples were scanned by the SEM (Hitachi SU8010).…”
Section: Methodsmentioning
confidence: 99%